2015
DOI: 10.1002/cphc.201500096
|View full text |Cite
|
Sign up to set email alerts
|

Airbrush Formation of Liquid Crystal/Polymer Fibers

Abstract: A homogeneous solution of a low-molecular-weight liquid crystal and a polymer spontaneously phase separates during airbrushing to form uniform fibers with a fluid liquid-crystal core surrounded by a solid polymer sheath. This structure forms because it effectively minimizes the interfacial energy of the phase-separated components while minimizing the elastic energy of the liquid-crystal core. These fibers incorporate the sensitive stimuli response of liquid crystals while maintaining the structural integrity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…19,59 Research groups have also used SBS to airbrush fibers with liquid crystal cores and polymer shells formed through spontaneous phase separation during the spraying process. 60 …”
Section: Structure and Properties Of Fibersmentioning
confidence: 99%
“…19,59 Research groups have also used SBS to airbrush fibers with liquid crystal cores and polymer shells formed through spontaneous phase separation during the spraying process. 60 …”
Section: Structure and Properties Of Fibersmentioning
confidence: 99%
“…Lagerwall et al first reported incorporation of low molecular weight liquid crystal into a fiber using coaxial electro-spinning [5]. Our group has reported forming fibers from a single, homogeneous solution of liquid crystal and polymer dissolved in a common solvent using either electrospinning [6] or gas jet spinning [7]. In this paper, we report fabrication of functional fabrics that change color at varying temperatures.…”
Section: Introductionmentioning
confidence: 90%
“…LCs have been incorporated as the core of a fiber using single-needle electrospinning, [4,5] coaxial electrospinning, [6,7] and airbrushing. [8] The diameter of electrospun and airbrushed fibers is typically less than 10 µm, restricting the diameter of the LC core to single micron dimensions. Cholesteric liquid crystals (CLCs) are chiral and can have helical pitch in the sub-micrometer range, leading to selective reflection and color depending on the pitch.…”
Section: Doi: 101002/adma201902168mentioning
confidence: 99%